2012
DOI: 10.5194/acp-12-5949-2012
|View full text |Cite
|
Sign up to set email alerts
|

DOAS measurements of formaldehyde and glyoxal above a south-east Asian tropical rainforest

Abstract: Abstract. Tropical rainforests act as a huge contributor to the global emissions of biogenic volatile organic compounds (BVOCs). Measurements of their oxidation products, such as formaldehyde (HCHO) and glyoxal (CHOCHO), provide useful indicators of fast photochemistry occurring in the lower troposphere. However, measurements of these species in tropical forest locations are extremely limited. To redress this, HCHO and CHOCHO were measured using the longpath (LP) and multi-axis (MAX) differential optical absor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 62 publications
3
43
1
Order By: Relevance
“…The top-10 precursor NMHCs of HCHO and CHOCHO in terms of their production rate are listed in Table 2. Compared to similar studies (e.g., Volkamer et al, 2010;Huisman et al, 2011;Washenfelder et al, 2011;MacDonald et al, 2012;Parrish et al, 2012), anthropogenic and biogenic sources contribute almost equally to the chemical formation of HCHO and CHOCHO at the BG site. However, production of HCHO and CHOCHO from anthropogenic precursors is larger than from isoprene before noon; in the afternoon, the contribution of isoprene to HCHO and CHOCHO production becomes higher than from anthropogenic NMHCs.…”
Section: Hcho and Chocho Simulation By The Model Base Casementioning
confidence: 90%
See 2 more Smart Citations
“…The top-10 precursor NMHCs of HCHO and CHOCHO in terms of their production rate are listed in Table 2. Compared to similar studies (e.g., Volkamer et al, 2010;Huisman et al, 2011;Washenfelder et al, 2011;MacDonald et al, 2012;Parrish et al, 2012), anthropogenic and biogenic sources contribute almost equally to the chemical formation of HCHO and CHOCHO at the BG site. However, production of HCHO and CHOCHO from anthropogenic precursors is larger than from isoprene before noon; in the afternoon, the contribution of isoprene to HCHO and CHOCHO production becomes higher than from anthropogenic NMHCs.…”
Section: Hcho and Chocho Simulation By The Model Base Casementioning
confidence: 90%
“…Based on satellite observations, Vrekoussis et al (2010) conclude that regions with R GF lower than 0.045 are under influence of anthropogenic emissions, whereas R GF higher than 0.045 often indicates that VOC emissions mostly originate from biogenic sources. Average R GF up to 0.2-0.4 were observed by MacDonald et al (2012) in an Asian tropic forest. However, after analyzing the measured R GF and relevant trace gases at a rural site, DiGangi et al (2012) found that higher R GF corresponded to increased anthropogenic impact on local photochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the glyoxal retrieval using DOAS, several different analysis procedures have been commonly used [Sinreich et al, 2010;Li et al, 2012;Liu et al, 2012;MacDonald et al, 2012]. Most of the retrievals involve two major CHOCHO absorption bands including one at about 440 nm and the relatively strong band at around 455 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Initial interest in glyoxal within the atmospheric boundary layer was generated by reports of elevated concentrations at urban locations [Grosjean et al, 1990;Volkamer et al, 2005a;Sinreich et al, 2007] and in forest environments [Huisman et al, 2011;MacDonald et al, 2012], with peak levels ranging between a few hundred parts per trillion (pptv, equivalent to pmol mol À1 ) to low parts per billion (ppbv, equivalent to nmol mol À1 ) observed using ground-based instruments. Satellite observations have also been reported using the Scanning Imaging Absorption Spectrometer for Atmospheric Cartography [Wittrock, 2006;Wittrock et al, 2006], the Ozone Monitoring Instrument (K. Chance, personal communication, 2013), and the Global Ozone Monitoring Experiment-2 [Lerot et al, 2010;Vrekoussis et al, 2010].…”
Section: Introductionmentioning
confidence: 99%